ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN STOCK BAHAN BAKU - Richard Andrew (Jurnal Trial Balance, 2024)
Abstract The purpose of this study was to determine the purchase accounting information system that has been done by Upstreet Foodhub and enter data into the accounting information system that should be done by Upstreet Foodhub. The research method used is descriptive analysis. This method is an analysis of data carried out directly at the research site, then compared with existing theories to analyze a conclusion that can be obtained and the results obtained. This study was conducted on stol research on Upstreet Foodhub. The results showed that there are many errors or human error from management accounting information systems to make mistakes, often the result of poor inventory and human error at the time of repair of raw materials. It should be fixed with existing internal improvements so that the threat of the system can be addressed thoroughly.